CoWIN twitter dataset: A comprehensive collection of public discourse on India's COVID-19 vaccination platformMendeley Data - Shubham Mittal; Swarnalakshmi Umamaheswaran (Data in Brief)
The CoWIN Twitter Dataset offers a wide-ranging collection of public opinions on India's COVID-19 vaccination platform CoWIN. The raw dataset has 635,000 tweets that mention “cowin,” collected over the period of January to December 2021. The dataset was extracted by employing the Twitter Academic API. It addition to the raw data, it also included a cleaned and processed set of 419,409 English tweets, and a labeled subset with sentiment analysis. The raw data file has tweet details like ID, text, timestamp, user ID, and language. The processed dataset is devoid of URLs and hashtags and other noise, and also adds month and category groupings. Finally,the labelled dataset gives sentiment classifications of positive or negative the relevant tweets. This dataset enables researchers to analyse themes and sentiments related to India's vaccination administration. It can help policymakers gain insights around issues related to large-scale health initiatives and digital health systems. The mix of languages in the data also makes it useful for language processing research.